Examine the Effects of a 50% Methanolic Extract of Acacia Arabica on the Quantity and Quality of Sperm Produced by Male Rattus Norvegicus - Qureshi, Alka; Singh, Sonalika; Goswami, Anjali (Journal of Neonatal Surgery, 2025)
The present study investigates the antifertility potential of Acacia arabica (babul) through the administration of its 50% methanolic bark extract in male Rattus norvegicus (albino Wistar rats). Plant-based contraceptives are increasingly gaining attention due to their accessibility, safety profile, and reduced side effects compared with synthetic alternatives. In this context, A. arabica, a plant rich in tannins, flavonoids, glycosides, and saponins, was evaluated for its impact on male reproductive physiology. Adult male rats (150–200 g) were randomly divided into four groups: a control group (vehicle-treated) and three experimental groups receiving A. arabica extract orally at doses of 100, 200, and 300 mg/kg body weight for 60 days. Standardized semen analysis was conducted to assess sperm count, motility, progressive motility, viability, morphology, semen pH, and volume. Data were analyzed using one-way ANOVA followed by post hoc tests, with p < 0.05 considered significant. Results revealed a dose-dependent decline in sperm quality and quantity. The control group recorded the highest sperm count (95 million/mL), motility (93%), and viability (95%). In contrast, the 300 mg/kg group demonstrated significant reductions in sperm count (60 million/mL), motility (76%), progressive motility (60%), and viability (78%). Normal sperm morphology also declined from 98% in the control to 81% at 300 mg/kg. Semen volume decreased progressively across treated groups, while semen pH showed minor shifts toward acidity. These findings indicate that methanolic extract of A. arabica exerts pronounced antispermatogenic and antifertility effects in male rats, likely mediated through disruption of spermatogenesis and hormonal regulation. The study supports traditional claims of A. arabica as a natural contraceptive and highlights its potential as a candidate for developing safer, reversible, and plant-based male contraceptive agents. Further investigations are warranted to elucidate the underlying mechanisms and ensure safety for clinical translation